Learning rates and mathematics achievement in Chile - María José Ramírez (Universidad Autónoma de Madrid, 2016)
Using data from the Trends in International Mathematics and Science Study (TIMSS), this paper analyzes the mathematics knowledge and skills of a nationally representative sample of Chilean students in the 7th and 8th grades. The results show a significant increase in mean achievement between the two grades. If this learning rate were projected beyond the 8th grade, it is clear that the Chilean students are lagging three years behind compared to countries like Italy or New Zealand. A substantial gap between the Chilean curricular objectives and the students' accomplishments is also noted. The emphasis the teachers place on the mastery of basic mathematics skills seems to be jeopardizing the opportunities the students have to learn more advanced mathematics topics. The findings show that schools with their own written statement of the curriculum attained significantly higher mathematics achievement. The provision of differentiated instruction did not have a significant association with achievement. Keywords: mathematics achievement - achievement gains - curriculum - Chile   Ritmos de aprendizaje y rendimiento en Matemáticas en Chile Usando datos del Estudio Internacional de Tendencias en Matemáticas y Ciencias, este trabajo analiza el rendimiento en matemáticas de una muestra representativa a nivel nacional de alumnos de séptimo y octavo básico en Chile. Los resultados muestran que hay una diferencia significativa entre los rendimientos promedios de ambos niveles. Si esta diferencia se proyecta más allá de octavo, los alumnos chilenos necesitarían tres años para lograr un desempeño similar al de sus pares de Italia o Nueva Zelanda. Tomando como criterio los objetivos del curriculum nacional, este estudio también muestra que los alumnos chilenos saben mucho menos de lo esperado para su nivel. Como consecuencia del mayor énfasis que los profesores ponen en el manejo de habilidades básicas, los alumnos parecen no tener suficientes oportunidades para aprender matemáticas más avanzadas. Los colegios que cuentan con una propuesta curricular propia, obtienen mejor rendimiento en matemáticas. El ofrecer un tipo de instrucción diferenciada no se asocia a variaciones en el rendimiento promedio de los colegios. Descriptores: rendimiento en matemáticas - logro en rendimiento - Chile